An Inverted Container in Containing and Not Containing Hospitalized Patients—A Multidisciplinary Narrative Inquiry - Gabay, Gillie; Ben-Asher, Smadar (Frontiers in Public Health, 2022)
Objective: Patient-centered care calls to contain patients in their time of crisis. This study extends the knowledge of provider-patient interactions in the hectic environment of acute care applying Bion's container-contained framework from psychoanalysis. Methods: Following ethical approval, we performed a narrative inquiry of the experiences of ten patients upon discharge from lengthy hospitalizations in acute care. Interviews were conducted upon discharge and about one-month post-discharge. Findings: Data analysis suggests four modes of containing of patients by providers. In nurturing interactions, typical of an active container-contained mode, patients experienced humanized care, symptom control, hope, and internal locus of control. This mode yielded patient gratitude towards providers, wellbeing, and post-discharge self-management of diseases. In rigid and wall-free modes of containing, patients experienced a sense of powerlessness and discomfort. A new mode of container-contained was identified, the 'Inverted Container', which extends Bion's theory and contradicts patient-centered care. In inverted containers, patients contained the providers yet reported feeling gratitude towards providers. The gratitude constitutes a defense mechanism and reflects a traumatic experience during hospitalization, which led to post-discharge distrust in providers and hospitals and poor self-management of illness. Conclusions: To effectively provide patient-centered care, provider-patient interaction in lengthy hospitalizations must move along a clinical axis and a relationship axis. This shifting may facilitate containing patients in their time of crisis so essential processes of reflection, projection, and transference are facilitated in-hospital care.